The voices of those who served: The early war years and the men of the 1st Battalion, Cameron Highlanders of Ottawa (MG). - Morrison, Gloria Alice. (University of Ottawa (Canada), 2001)
The intent of this endeavor is to consider the Second World War from the perspective of one group of men who served with a machine gun regiment based out of Ottawa. The objective is to rediscover what the early war experience was like for these Canadian soldiers. All the questions considered in this undertaking may be subsumed into three basic queries: Who were these men who came forward to serve? Why had they 'volunteered' to go to war? And, what were the early war years like for these predominantly young Canadians? The third query comprises the bulk of the attention in this thesis. The time period under review is from September 1939 until May of 1941. This covers the mobilization period in Ottawa and the unit's first overseas posting in Iceland. This time frame concerns an overlooked aspect of war service---the induction and foundation period for Canadian Armed Forces. (Abstract shortened by UMI.)
Keywords: History, Canadian.